AUDIT DELAY ANALYSIS THROUGH LISTING AGE, AUDIT COMMITTEE, AUDIT TENURE AND SUBSIDIARIES - Ika Farida Ulfa; Titin Eka Ardiana (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The purpose of the implementation of this research was to determine the effect of the independent variables, namely the age of listing, audit committee, audit tenure and holding company on the dependent variable, namely audit delay. This research is a quantitative research. The populations in this research were all manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2014-2017, totaling 115 companies in the manufacturing sector. Sampling in this research is using purposive sampling method. Based on this method, the number of manufacturing companies that were sampled in this research amounted to 79 companies. This research uses data collection methods with the documentation method, namely by taking secondary data that already exists in financial reports (Financial Reports) on manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017. Technical analysis of the data in this research uses multiple linear regression method with the help of SPSS computer application. The findings of this research are listing age has a positive effect on audit delay, while audit committees, audit tenure and holding companies have a negative effect on audit delay Keywords: listing age, audit committee, audit tenure, subsidiaries, audit delay